Anti-PCSK9 antibodies for the treatment of heterozygous familial hypercholesterolemia: Patient selection and perspectives - Catapano, A.; Pirillo, A.; Norata, Giuseppe (2017)
© 2017 Catapano et al. Heterozygous familial hypercholesterolemia (FH) is a genetic disorder characterized by high low-density lipoprotein cholesterol levels from birth, which exposes the arteries to high levels of atherogenic lipoproteins lifelong and results in a significantly increased risk of premature cardiovascular events. The diagnosis of FH, followed by an appropriate and early treatment is critical to reduce the cardiovascular burden in this population. Phase I-III clinical trials showed the benefit of proprotein convertase subtilisin kexin 9 inhibitors, both alirocumab and evolocumab, in these patients with an average low-density lipoprotein cholesterol reduction ranging from −40% to −60%. The aim of this review is to address the unmet needs in cholesterol management, elucidate the biology and the clinical benefit of proprotein convertase subtilisin kexin 9 inhibition and finally discuss the open gaps and future directions in the treatment of patients with heterozygous FH.